Otomasi Layanan Perpustakaan Sekolah Untuk Peningkatan Literasi Kesehatan Reproduksi Remaja di SMA 1 Muhammadiyah Jakarta Pusat - Wardiyono Wardiyono; Indah Kurnianingsih; Danang Dwijo Kangko; Nita Ismayati; Dani Awaludin N; M. Ishom Kamil; David I . Ardiansyah; Kemal S. Radhoto; Clara Priscillia (Info Abdi Cendekia, 2020)
This progam aims to improve health literacy of students at SMA 1 Muhammadiyah Central Jakarta through the implementation of school library automation. Using library automation to support the library services, this program tries to support the availability of health information sources to increase health literacy on adolescent reproductive health problems which are very much needed for students. The implementation activities include are: supporting technical problem solving related to library automation, increasing the content of the library to support health literacy, and increasing the competence and capacity of school library managers. These are considered still lacking in SMA 1 Muhammadiyah. Its also involved students with repackaging health literacy resources. 18 students of the YARSI University Library Science study program involved in the activities. The progam itself acts as the first step of implementation the Real Work Lecture (KKN). A total of 364 titles, 3810 copies, the school library collections had their bibliographic data processed into the SchILS application. In addition, students also made 11 Repackaged Information products in the forms of videos and infographics related to adolescent reproductive health education. A pathfinder for Adolescent Reproductive Health has been successfully developed as a tool to improve adolescent reproductive health literacy. In the long term, the KKN program will be followed up by updating the SchILS software and maintaining its content. The extend outcome of the program expects other agencies such as the Health Office, Puskesmas, and other schools can access the content for health information that has been compiled, in the light of more widespread dissemination.